Respiratory Syncytial Virus (RSV) Fusion Protein Subunit F2, Not Attachment Protein G, Determines the Specificity of RSV Infection - Schlender, Jörg (American Society for Microbiology, 2003)
Human respiratory syncytial virus (HRSV) and bovine RSV (BRSV) infect human beings and cattle in a species-specific manner. We have here analyzed the contribution of RSV envelope proteins to species-specific entry into cells. In contrast to permanent cell lines, primary cells of human or bovine origin, including differentiated respiratory epithelia, peripheral blood lymphocytes, and macrophages, showed a pronounced species-specific permissivity for HRSV and BRSV infection, respectively. Recombinant BRSV deletion mutants lacking either the small hydrophobic (SH) protein gene or both SH and the attachment glycoprotein (G) gene retained their specificity for bovine cells, whereas corresponding mutants carrying the HRSV F gene specifically infected human cells. To further narrow the responsible region of F, two reciprocal chimeric F constructs were assembled from BRSV and HRSV F1 and F2 subunits. The specificity of recombinant RSV carrying only the chimeric F proteins strictly correlated with the origin of the membrane-distal F2 domain. A contribution of G to the specificity of entry could be excluded after reintroduction of BRSV or HRSV G. Virus with F1 and G from BRSV and with only F2 from HRSV specifically infected human cells, whereas virus expressing F1 and G from HRSV and F2 from BRSV specifically infected bovine cells. The introduction of G enhanced the infectivities of both chimeric viruses to equal degrees. Thus, the role of the nominal attachment protein G is confined to facilitating infection in a non-species-specific manner, most probably by binding to cell surface glycosaminoglycans. The identification of the F2 subunit as the determinant of RSV host cell specificity facilitates identification of virus receptors and should allow for development of reagents specifically interfering with RSV entry.